Solution of the initial problem for a differential equation of fractal oscillator - V. D. Beybalaev (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2009)
This article provides a synthesis of the problem of harmonic oscillator with damping based on differential equations with fractional differentiation and demonstrates the possibility of consideration of nonlinear oscillatory processes on their basis.